Design and implementation of an electronic stimulator - del Carpio Salinas, Jorge (2005)
The project was developed within the frame and standards that are included in the field of studies ofthe medicine; its internal architecture designed using integrated circuits compact, so is the case of the generator of signals ICL8038, that provides three types of signal of variable frequency, to thisadds the implementation of an amplifying stage conformed by CI STK086, that maintains the frequency and signal form to amplify itself. The implemented electronic estimulador has the capacity to generate three types of electrical signal (sine, triangular and square) and simultaneously these have thecharacteristics to vary its Amplitude and frequency for this way being applied to weaves of alive organisms and to analyze its physical and electrical behavior.